A continent of and for whiteness?: “White” colonialism and the 1959 Antarctic Treaty - Mancilla, Alejandra (Polar Record, 2019)
There are at least four ways in which Antarctic colonialism was white: it was paradigmatically performed by white men; it consisted in the taking of vast, white expanses of land; it was carried out with a carte blanche (literally, “blank card”) attitude; and it was presented to the world as a white, innocent adventure. While the first, racial whiteness has been amply problematised, I suggest that the last three illuminate yet other moral wrongs of the Antarctic colonial project. Moreover, they might be constitutive of a larger class of “white” colonialisms beyond the White Continent.
Keywords: Antarktis; historie; politikk; samfunnsfag

The moral limits of territorial claims in Antarctica - Mancilla, Alejandra (Ethics & International Affairs, 2018)
By virtue of the Antarctic Treaty, signed in 1959, the territorial claims to Antarctica of seven of the original signatories were held in abeyance or “frozen.” Considered by many as an exemplar of international law, the Antarctic Treaty System has come to be increasingly questioned, however, in a very much changed global scenario that presents new challenges to the governance of the White Continent. In this context, it is necessary to gain a clearer understanding of the moral weight of those initial claims, which stand (despite being frozen) as a cornerstone of the treaty. The aim of this article is to offer an appraisal of such claims, which may be divided into two main kinds: those grounded on some relevant link to the territory, and those grounded on official documents and geographical doctrines. After pointing to the limitations and challenges that they face, I conclude with some remarks about how this assessment ought to serve as a starting point to rethink the territorial status of Antarctica.
Keywords: Antarktis; historie; jus; politikk; ressurser

Norske interesser og politikk for Bouvetøya - [s.n.] (Justis- og beredskapsdepartementet, 2015)
Helt siden Bouvetøya ble norsk biland i 1930 har denne øya langt sør i Atlanterhavet vært del av vår polare identitet og historie. Gjennom tidene har øya likevel ikke vært gjenstand for stor oppmerksomhet. Siden 1930 har det heller ikke vært gitt noen samlet omtale til Stortinget av forhold som angår forvaltningen av dette området. Regjeringen mener det nå er tid for å gjøre Bouvetøya bedre kjent gjennom en melding til Stortinget. Denne meldingen har derfor som mål å beskrive Bouvetøya, og gi en bred fremstilling av ulike forhold når det gjelder rettslige rammebetingelser, forvaltning og aktivitet på øya og i havområdene rundt. Regjeringen fremmer også en melding til Stortinget som omhandler norske interesser og politikk i Antarktis, herunder de norske bilandene Dronning Maud Land og Peter I Øy, heretter omtalt som Antarktismeldingen. 1 Tradisjonelt har de tre bilandene Bouvetøya, Dronning Maud Land og Peter I Øy vært omtalt sammen. Bouvetøya ligger nord for Antarktistraktatens virkeområde, og er ubestridt norsk territorium. Regjeringen har derfor funnet det hensiktsmessig å legge frem en egen melding om norske interesser og politikk for Bouvetøya. Spørsmål som gjelder Bouvetøya håndteres som en integrert del av norsk politikk. Dette inne- bærer å gjøre norsk lovgivning gjeldende for øya i den grad det er hensiktsmessig, og å sørge for at lovgrunnlaget er tilpasset behovene. I denne meldingen om Bouvetøya beskrives intern lovgivning så vel som det folkerettslige rammeverket, og ret- tighetene og pliktene som følger av dette, herunder retten til naturressurser og plikten til å ta vare på miljøet. Det gis en egen omtale av de stats- rettslige sidene ved øya, og av at det vil bli vurdert om disse og andre forhold bør reguleres i en egen lov.
Tilråding fra Justis- og beredskapsdepartementet 12. juni 2015, godkjent i statsråd samme dag. (Regjeringen Solberg)
Keywords: Bouvetøya; forvaltning; lovgivning; overvåking; politikk; økonomi

Inspeksjonsordningen under Antarktistraktaten - Bech, Jon (Polarboken, 2014)
Keywords: Antarktis; jus; politikk

Norge i Antarktis - Rognhaug, Magnus Hovind (red.) (Norsk Polarinstitutt, 2014)
Keywords: Antarktis; Antarktistraktaten; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Sørishavet; forskning; miljøvern; polarforskning; politikk

Whaling, lobbying and politics - Ringstad, Jan Erik (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalindustri; pelagisk; politikk

Da Norge annekterte Bouvetøya - Skagestad, Odd Gunnar (Historie (Bergen), 2013)
Keywords: Bouvetøya; historie; politikk

Hvordan Bouvetøya ble norsk - Skagestad, Odd Gunnar (UD-posten: husorgan for utenrikstjenesten, 2013)
Keywords: Bouvetøya; historie; politikk

Vår sydligste provins: Dronning Maud Land 75 år - Skagestad, Odd Gunnar (Historie (Bergen), 2013)
Keywords: Dronning Maud Land; historie; politikk

A frozen field of dreams : science, strategy, and the Antarctic in Norway, Sweden, and the British empire, 1912-1952 : a dissertation submitted to the Department of History and the Committee on graduate studies of Stanford University in partial fulfillment of the requirements for the degree of Doctor of Philosophy - Roberts, Peder (Peder William Chellew Roberts, 2010)
Volume: Dr. Phil.
Keywords: Antarktis; Norge; historie; norske ekspedisjoner; politikk

Antarktistraktatens effekt på norsk politikk 1959-2009: fra polarimperium på sparebluss til nye utfordringer - og ny giv? - Skagestad, Odd Gunnar (Norsk militært tidsskrift, 2010)
Keywords: Antarktis; politikk